2003
DOI: 10.5032/jae.2003.02038
|View full text |Cite
|
Sign up to set email alerts
|

The Future Role Of Instructional Technology In Agricultural Education In North Carolina And Virgina

Abstract: The purpose of this study was to assess teachers' perceptions regarding the future of instructional technology in secondary school agricultural education programs in North Carolina and Virginia. A stratified random sample was selected from the populations of agricultural education teachers in North Carolina and Virginia. Likert-type scales were used to measure the future role instructional technology will play in agricultural education programs, the potential benefits of instructional technology, and the poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 3 publications
1
19
0
Order By: Relevance
“…Within each of these contexts, VR technology found its place as a method to help provide initial exposure to subject matter and to positively reinforce skill development. Alston et al (2003) found SBAE teachers expressed mixed perceptions about VR technology in SBAE. Since Alston et al's (2003) study, VR technology has changed considerably and has become more widely accepted and used in educational settings (Bailenson, 2018;Potkonjak et al, 2016).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Within each of these contexts, VR technology found its place as a method to help provide initial exposure to subject matter and to positively reinforce skill development. Alston et al (2003) found SBAE teachers expressed mixed perceptions about VR technology in SBAE. Since Alston et al's (2003) study, VR technology has changed considerably and has become more widely accepted and used in educational settings (Bailenson, 2018;Potkonjak et al, 2016).…”
Section: Introductionmentioning
confidence: 91%
“…Barriers such as cost may inhibit educational technology adoption and use (Alston, Miller, & Williams, 2003;Coley, Warner, Stair, Flowers, & Croom, 2015;Williams et al, 2014b), which may result in missed opportunities for progress and change. Kotrlik, Redmann, and Douglas (2003) cautioned "that much more needs to be done to encourage and support [SBAE] teachers in the teaching/learning process" (p. 88).…”
Section: Introductionmentioning
confidence: 99%
“…Rogers (2000) found the lack of availability and accessibility of technology to teachers was one reason for the lack of use. McKendrick, Straquadine, and Hubert (2002) and Alston, Miller, & Williams (2003) both identified inadequate funding as a major barrier to integrating technology. Another moderate to major barrier to technology integration identified by 68.43% of teachers was time to develop lessons that use technology.…”
Section: Conclusion Recommendations and Implicationsmentioning
confidence: 99%
“…Rogers (2000) found the lack of availability and accessibility of technology to teachers was one reason for the lack of use. Alston, Miller, and Williams (2003) identified cost of software and equipment as the greatest barriers to integrating technology. Other identified barriers include a lack of access to reliable technology (An & Reigeluth, 2011;Inan & Lowther, 2010;Petko, 2012), limited planning time (An & Reigeluth, 2011, Kotrlik & Redmann, 2009b, not enough technology to accommodate students, scheduling constraints, and lack of appropriate technical support (Kotrlik & Redmann, 2009a, Kotrlik & Redmann, 2009b.…”
mentioning
confidence: 99%
“…Many models and methods can be used for collecting the information necessary to establish competency models in agriculture education programs. Alston, Miller, and Williams (2003) stated, "The profession of agricultural education has a clear philosophy with several distinguishing tenants. Emphasis is placed on solving problems in real-world settings, learning by doing, individualized learning, career guidance, leadership and citizenship development, and community-oriented programs" (Phipps & Osborne, 1988).…”
Section: Agricultural Mechanics Trendsmentioning
confidence: 99%